1994
DOI: 10.1021/j100092a006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence by Optical Spectroscopy and EPR for the Light-Induced Conformational Isomerization of 2-Naphthylphenylcarbene in n-Heptane Shpolskii Matrix

Abstract: The quasi-line fluorescence and excitation spectra of 2-naphthylphenylcarbene (2-NPC) in n-hexane and n-heptane Shpolskii matrices at 4.2 K are composed of several spectra with origins shifted by 30-300 cm-' from each other. They have been attributed to the triplet-triplet transition of the syn and anti conformers of 2-NPC, each one being trapped in several different sites of the matrix. This attribution has been confirmed by the EPR experiments performed at 77 K. Furthermore, the fluorescence and EPR spectra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
9
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 4 publications
5
9
0
Order By: Relevance
“…The energy barriers for the conversion of these forms into each other are 395 cm-' (pseudo E/trans + pseudo Ucis) and 458 cm-I (pseudo Zlcis + pseudo E/trans). Our previous experimental results (16) indicated that, in the n-heptane Shpolskii matrix, the species fluorescing at 589.5 nm converts thermally at 90 K (corresponding to 60 cm-I) into the species fluorescing at 600.5 nm. Therefore, the actual energy barrier should be smaller than our theoretical SCF value.…”
Section: Ground State Energeticsmentioning
confidence: 95%
See 4 more Smart Citations
“…The energy barriers for the conversion of these forms into each other are 395 cm-' (pseudo E/trans + pseudo Ucis) and 458 cm-I (pseudo Zlcis + pseudo E/trans). Our previous experimental results (16) indicated that, in the n-heptane Shpolskii matrix, the species fluorescing at 589.5 nm converts thermally at 90 K (corresponding to 60 cm-I) into the species fluorescing at 600.5 nm. Therefore, the actual energy barrier should be smaller than our theoretical SCF value.…”
Section: Ground State Energeticsmentioning
confidence: 95%
“…In the case of 2-NPC, the second excited triplet state T2 is separated from the TI state by 0.7 1 eV (5727 cm-l) for the pseudo-E/trans conformer and by 0.72 eV (5808 cm-I) for the pseudo-Ucis conformer. This large separation explains why the quasi line fluorescence spectra of both conformers exhibit mirror-image symmetry with the corresponding excitation spectra, as far as vibrational frequencies up to 1700 cm-' are concerned (16). Such a mirror-image symmetry does not exist for DPC (see Fig.…”
Section: Transition Energies Of the Conformersmentioning
confidence: 96%
See 3 more Smart Citations